Availability and accessibility of indigenous foods in Gauteng region, South Africa - Kesa, Hema; Tchuenchieu Kamgain, Alex D.; Zuma, Mthokozisi Kwazi; Mbhenyane, Xikombiso (Frontiers in Sustainable Food Systems, 2024)
While South Africa maintains national food security, food insecurity persists at the household level, with not all households having access to sufficient food. Proposals to address this include promoting the consumption of indigenous foods (IF). However, urbanization in the Gauteng region has sparked a nutrition transition, characterized by increased consumption of Western diets, resulting in rising rates of malnutrition and non-communicable diseases. This study sought to assess the availability and accessibility of indigenous foods in the region for residents. A quantitative cross-sectional research survey was conducted in the Gauteng region, involving 746 participants who provided insights into their ways of acquiring indigenous foods and rated their overall availability. Additionally, the survey gathered opinions on IF availability across different settings and collected suggestions for improving IF accessibility. Among a list of 18 South African indigenous foods, between 55.2 and 77.2% of participants did not know where they could be obtained. Acquisition through vendors, with a maximum of 14% of respondents, emerged as relatively more popular compared to food markets, spaza shops, supermarkets, and home gardens. The majority of surveyed participants (55%) perceived indigenous foods as unavailable in the region. Agreement rates for the availability of indigenous foods for sale or serving in various settings were 53.5% for supermarkets, 42% for schools, 44.2% for hospitals, and 37.5% for workplaces. Respondents suggested several strategies to enhance IF accessibility in the region, including marketing, home gardens, farms, supermarkets, education, elders, restaurants, and schools/universities. Overall, there is a need for increased education on the nutritional benefits of indigenous foods and the implementation of policies to improve their accessibility in urbanized provinces like Gauteng.